Work Stress Management Due to Fatigue Among Textile Workers - Atmojo, Tutug Bolet; Rinawati, Seviana; Rha, Warda Yussy; Sumardiyono; Wijanarti, Maria Paskanita; Ismayenti, Lusi; Suratna, Farhana Syahrotun Nisa; Gustav, Jordan Syah; Utomo, Bekti (IJESS International Journal of Education and Social Science, 2025)
Work stress in the workplace is an important issue that requires special attention, because if not properly managed, it can lead to various serious symptoms that affect employees’ health, productivity, and capability. The aims of research to analyze the relationship between fatigue and work stress. Methods: This research used a quantitative method with a cross-sectional design approach. The study was conducted from April to June 2025. The sampling technique used was random sampling with a sample of 41 respondents. Data were analyzed using the chi-square test. Results: Work stress was experienced by 46.34% of workers, and 48.78% experienced fatigue. Among those who were fatigued, 34.15% experienced work stress and 12.20% of non-fatigued workers experienced work stress. Meanwhile, 39.02% of non-fatigued workers did not experience work stress, and 14.63% of fatigued workers did not experience work stress. The significance test result showed p = 0.004, indicating that fatigue is related with work stress among textile workers.